Pengaruh Pengetahuan Keuangan, Sikap Keuangan, Locus Of Control, Efikasi Diri Keuangan Terhadap Perilaku Manajemen Keuangan pada Pelaku Ekonomi Kreatif Subsektor Kuliner (Studi Kasus pada Anggota IWAPI Kabupaten Malang) - Pratiwi, Rita Anggis; Susyanti, Jeni; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research is motivated by the rapid development of creative economy actors. So that creative economy MSME players are required to have the latest innovations and develop their businesses by utilizing increasingly advanced technological developments. However, there are still many creative economic actors who do not know how important financial knowledge, financial attitudes, locus of control, and financial self-efficacy are in a business. The purpose of this study was to determine the effect of financial knowledge, financial attitudes, locus of control, self-efficacy on financial management behavior.This research uses a quantitative descriptive method. This method aims to make a description or descriptive of a situation objectively. Respondents in this study were 60 people. The sampling technique was purposive sampling of IWAPI members. The results of this study reveal that financial knowledge has a significant effect on financial management behavior. While financial attitudes, locus of control, financial self-efficacy have no significant effect on financial management behavior. Keywords: Creative Economy, Financial Knowledge, Financial Attitude, Locus Of Control, Self-Efficacy, Financial Management Behavior.